Turbulent burning rates of gasoline components, Part 2 – Effect of carbon number. (1st March 2016) - Burluka, A.A.; Gaughan, R.G.; Griffiths, J.F.; Mandilas, C.; Sheppard, C.G.W.; Woolley, R.
Abstract: Experimental measurements of turbulent and laminar burning velocities have been made for premixed hydrocarbon–air flames of straight chain molecules of increasing carbon number (from n-pentane to n-octane). Measurements were performed at 0.5 MPa, 360 K and rms turbulent velocities of 2 and 6 m/s, for a range of equivalence ratios. The laminar burning velocities were used to interpret the turbulent data, but were also found to be broadly in line with those of previous workers. At lean conditions the turbulent burning velocity was measured to be similar between the four alkanes studied. However, at rich conditions there were notable differences between the turbulent burn rates of the fuels. The equivalence ratio of the mixtures at which the maximum burning velocities occurred in the turbulent flames was richer than that under laminar conditions. The equivalence ratio of the peak turbulent burning velocity was found to be a function of the carbon number of the fuel and the turbulent intensity and became gradually fuel rich with increases in each of these values.